Gregory of Nyssa: Ancient and (Post)modern. By Morwenna Ludlow - Meredith, Anthony (The journal of theological studies, 2010)
In this very thorough and up-to-date study of Gregory of Nyssa, Morwenna Ludlow tries to come to terms with ‘the Elusive Gregory’—a term she uses in the introduction. Gregory has been the subject of so many varied and incompatible interpretations that it is hard to discover the real man that underlies them all. In fact, if there is any criticism to be made of this very rich treatment of Gregory’s theology, it is that so much of the space is taken up with analyses of fairly recent scholarship, that the actual flow of the argument is hard to follow. After the introduction, the book is divided into four main sections: (1) the doctrine of the Trinity; (2) Christology; (3) sex, gender, and embodiment; (4) theology.